The unconscious a conceptual analysis - MacIntyre, Alasdair C. (Studies in philosophical psychology, 2004)
First published in 1958, 'The Unconscious' still ranks as one of the most important and clearly written philosophical inquiries into the fundamental concept of psychoanalysis.